Exploring stress levels and work-family conflict among parents of children with health issues : the moderating role of workplace social support and financial concerns - María Björg Fjölnisdóttir 2000- (2024)
This aim of this study was to examine daily stress levels, work-family conflict (WFC), social support in the workplace, and financial concerns among parents of children with health issues (CWHI) and parents of typically developing children. Furthermore, the moderating role of social support in the workplace and financial concerns in the relationship between having CWHI and daily stress was examined. The moderating role of social support in the workplace in the relationship between having CWHI and WFC was also examined. The data were gathered from a 2022 survey on health, well-being, and workplace attitudes among 1840 sick-listed workers in Iceland who received benefits in 2018 and 2019. The results indicated that parents of CWHI experienced higher stress levels, financial concerns and WFC. Higher support and fewer financial concerns were associated with lower daily stress levels among both parental groups. Higher support was associated with less WFC among both groups as well. However, parents of typically developing children experienced a greater decrease in both stress and WFC. Future studies should focus on the current state of employed parents of CWHI and examine further ways to contribute to their well-being. Keywords: parents of children with health issues, stress, social support in the workplace, financial concerns, work-family conflict Markmið þessarar rannsóknar var að skoða streitu, jafnvægi milli vinnu og einkalífs, fjárhagsáhyggjur og stuðning frá vinnustað hjá bæði foreldrum sem eiga börn með heilsufarsvanda og ekki. Þar að auki var skoðað sambandið á milli þess að eiga barn með heilsufarsvanda og streitu og hvernig stuðningur frá vinnustað og fjárhagsáhyggjur geta haft áhrif á sambandið þar á milli. Einnig var skoðað hvernig stuðningur frá vinnustað hefði áhrif á jafnvægið á milli vinnu og einkalífs hjá foreldrum barna með heilsufarsvanda. Unnið var með fyrirliggjandi gögn frá rannsókn VIRK á aðstæðum og líðan fólks sem fór í veikindaleyfi frá vinnu árin 2018 og 2019 en rannsóknin var framkvæmd ...